Penerapan Akuntansi Persediaan Pada PT Hutama Neala Di Surabaya: Laporan Kegiatan Kuliah Kerja Lapangan - Elvira Damayanti; Bambang Karnain P; Harsono Teguh (Universitas 45 Surabaya, 2024)
The development of companies in Indonesia has entered the era of globalization which is marked by increasing competition between business actors operating in various business fields, both in the trade and industrial services sector which is experiencing an increase in business activities. Every company, whether engaged in trading or manufacturing, generally aims to make a profit. Apart from these goals, the company must also maintain business continuity and growth so that the company can run well and develop. In an effort to achieve this goal, the company must be able to operate smoothly and be able to combine all existing resources, so that it can achieve optimal results and profit levels. One resource that plays an important role in achieving company goals is inventory. This is because most of the company's activities are related to inventory. Inventory is a current asset that has quite a high risk in the company's activities if it is not paid proper attention. The risks that may arise can be in the form of physical risks or financial risks. For example, from a physical perspective, namely if there is fraud regarding inventory in the warehouse due to lack of supervision and damage to goods occurs which results in disappointed consumers. And from a financial perspective, that is if an error occurs in recording which results in a company loss in the accounting period.